Realizing the mass public benefit of evidence-based psychological therapies: The IAPT program - Clark, D (Annual Reviews, 2018)
Empirically supported psychological therapies have been developed for many mental health conditions. However, in most countries only a small proportion of the public benefit from these advances. The English Improving Access to Psychological Therapies (IAPT) program aims to bridge the gap between research and practice by training over 10,500 new psychological therapists in empirically supported treatments and deploying them in new services for the treatment of depression and anxiety disorders. Currently IAPT treats over 560,000 patients per year, obtains clinical outcome data on 98.5% of these individuals, and places this information in the public domain. Around 50% of patients treated in IAPT services recover, and two-thirds show worthwhile benefits. The clinical and economic arguments on which IAPT is based are presented, along with details of the service model, how the program was implemented, and recent findings about service organization. Limitations and future directions are outlined.